Implementation of Adobe Flash Based Electronic Learning Media on The Learning Outcomes of Fourth-Grade Students at SDN Banyu Urip IX Surabaya - Leni Yuliana; Desi Eka Pratiwi; Maulana Rafi Rulis Saputra; Putri Apriliyah (FKIP - Universitas Riau, 2026)
This study aims to determine the learning outcomes of fourth grade students at SDN Banyu Urip IX Surabaya after the implementation of Adobe Flash-based electronic learning media, as well as to examine students’ responses toward the use of this media in the topic of energy transformation. This research employed a quantitative descriptive method with fourth-grade students of SDN Banyu Urip IX Surabaya as the research subjects. Data were collected through observation, documentation, tests, and questionnaires. The Adobe Flash-based learning media were developed to present the material interactively using engaging animations and visuals designed to enhance students’ conceptual understanding. Data analysis was carried out by calculating the percentage of learning outcomes and students’ responses toward the use of the media. The findings indicate that the implementation of Adobe Flash-based learning media improved students’ learning outcomes above the minimum standard and received positive responses from the students. The media were considered attractive, easy to use, and effective in helping students better understand the concept of energy transformation. In conclusion, the use of Adobe Flash based electronic learning media is effective in improving learning outcomes and student motivation in elementary science learning.